Reshaping of Dating Culture through the Presence of Online Dating Application - Swandari, Clevaria Ery; Susilastuti, Dewi H. (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
Online dating is an inevitable phenomenon in this digital age. The close interaction of digital natives with the internet makes them seem to entrust all activities in their lives to the internet, including dating and finding a mate. This makes them more likely to use online dating applications. This thesis investigates the drivers of the use of online dating applications by the digital natives, their opinions about online dating application and how the use of such application is different or the same between Indonesians and Americans. Data collection techniques are using questionnaire and interview. The secondary data in this study were obtained from other sources such as research results presented on the official website. This research found that there are many factors that influence digital natives in using online dating applications. This study reveals an array of eastern philosophical ideas, such as the predominance of female gendered application users in Indonesia, which implies that the gender line has become more ambiguous.